Association between dietary selenium intake and the prevalence of hypertension: results from the National Health and Nutrition Examination Survey 2003–2018 - Wu, Yilin; Yu, Zongliang (Frontiers in Immunology, 2024)
Aim The epidemiological evidence regarding the impact of dietary selenium intake on hypertension continues to be a subject of controversy. Our objective is to examine the correlation between dietary selenium intake and the prevalence of hypertension within a substantial and diverse population in the United States. Methods We carried out a cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES) to assess the association between dietary selenium intake and hypertension prevalence. Weight logistic regression analysis and smooth curve fitting were utilized to explore potential linear relationships. Subgroup analysis was further employed to investigate potential differences in this relationship across populations and assess potential synergies. Results The study included 32,928 individuals, and the average dietary selenium intake was 1.12 ± 0.53 μg. The prevalence rate of hypertension was 36.55% overall and decreased with the higher dietary selenium intake quartiles (quartiles 1, 40.25%; quartiles 2, 37.71%; quartiles 3, 36.04%, quartiles 4, 32.23%, p < 0.001). Each quartile increase in dietary selenium intake associated with 11% decreased the likelihood of prevalence of hypertension [OR = 0.89; 95% CI: 0.80–1.00; p = 0.0425]. Subgroup analyses revealed that there was no significant correlation between gender, age, body mass index, smoking status, alcohol consumption, and diabetes mellitus in relation to the association between dietary selenium intake and the prevalence of hypertension. Conclusion The prevalence of hypertension in adults was found to be linearly and negatively correlated with dietary selenium intake. In order to improve the prevention and treatment of hypertension, greater emphasis should be placed on selenium consumption.